Highly efficient concerted evolution in the ribosomal DNA repeats: Total rDNA repeat variation revealed by whole-genome shotgun sequence data - Ganley, Austen R.D.; Kobayashi, Takehiko (Genome Research, 2007)
Repeat families within genomes are often maintained with similar sequences. Traditionally, this has been explained by concerted evolution, where repeats in an array evolve “in concert” with the same sequence via continual turnover of repeats by recombination. Another form of evolution, birth-and-death evolution, can also explain this pattern, although in this case selection is the critical force maintaining the repeats. The level of intragenomic variation is the key difference between these two forms of evolution. The prohibitive size and repetitive nature of large repeat arrays have made determination of the absolute level of intragenomic repeat variability difficult, thus there is little evidence to support concerted evolution over birth-and-death evolution for many large repeat arrays. Here we use whole-genome shotgun sequence data from the genome projects of five fungal species to reveal absolute levels of sequence variation within the ribosomal RNA gene repeats (rDNA). The level of sequence variation is remarkably low. Furthermore, the polymorphisms that are detected are not functionally constrained and seem to exist beneath the level of selection. These results suggest the rDNA is evolving via concerted evolution. Comparisons with a repeat array undergoing birth-and-death evolution provide a clear contrast in the level of repeat array variation between these two forms of evolution, confirming that the rDNA indeed does evolve via concerted evolution. These low levels of intra-genomic variation are consistent with a model of concerted evolution in which homogenization is very rapid and efficiently maintains highly similar repeat arrays.
10.1101/gr.5457707